Rediscovery of Brazilian corambids (Gastropoda: Onchidorididae) - Cunha, Carlo M.; Saad, Luiza O. [UNESP]; Lima, Patrícia O.V. (Cambridge University Press (CUP), 2014)
Three specimens of the genus Corambe were found in the intertidal zone of Santos, São Paulo (Brazil); two of them were identified as C. evelinae and one as C. carambola. Both species are reported for the first time since more than about 40 years ago. © Marine Biological Association of the United Kingdom, 2014.
Keywords: Biodiversity; Brazil; Corambe; Gastropoda; Nudibranchia